Promoting Eclectic Method to Raise Learners’ Language Awareness in Speaking Skill - Irwandi Irwandi (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Speaking skill has been considered as the most challenging of the four language skills.  This skill contains a complex process of constructing meaning and requires learners to produce utterances not only correct linguistically but also appropriate pragmatically. To achieve the target, the learners need to be trained to have knowledge about language consciously (language awareness). For this reason, there is a need for considerable amount of effort required to create an appropriate method for teaching speaking without depending on one specific method or approach of teaching.  In this case, the use of eclectic method can be considered as one of alternative methods which involves the use of a variety of language teaching methods. The eclectic method was introduced in the beginning of 1990’s and became fashionably popular these days. The appearance of method is enhanced by the fact that every method of language teaching has strength and limitation. The eclectic method is a combination of different method of teaching and learning. Several different teaching methods are used to be adapted based on needs and abilities of learners. Effectively, this method also belongs to any kind of learners’ strength and learning style with the irrespective of age and level. This paper is aimed at discussing about the practical considerations of applying eclectic method in term of rising learners’ language awareness in oral communication skill. The discussion is begun form the advances that have been made in teaching of speaking over the last decades. It then considers how this knowledge becomes the basis for teaching speaking based on eclectic method.